STUDY ON QUALITY CHANGES OF LEMEA DURING STORAGE IN VARIOUS TYPES OF TEMPERATURE AND PACKAGING MATERIALS - Kurnia Herlina Dewi; Yessy Rosalina; Sutra Firansyah (BPFP Faperta UNIB, 2013)
Lemea is a traditional food from Rejang tribes that needs improvement in packaging so that the product can compete with other packaged foods. A study to get the proper packaging to maintain lemea’s quality using various types of packaging materials and storage temperatures is necessary to be conducted. The objective of this study is to examine effect of various types of packaging materials and storage temperature on quality changes of lemea. The study designed using CRD with 2 factors and 3 replications. Type of packaging material used in this research is LDPE plastic with a thickness of 0:01 mm, OPP / PP multilayer plastic with a thickness of 0.05 mm and PETE plastic bottles with a thickness of 1:25 mm; storage temperature used is room temperature at 27-32 °C and refrigerator temperature at 12-15 °C. Parameters measured were changes in water content, pH value, the number of colonies of microbes and organoleptic (color, scent, shape and overall acceptance attributes of lemea) on lemea that stored for 28 days with the observation point on day 7, 14, 21 and 28. Various of packaging materials of lemea are LDPE plastic, OPP / PP multilayer plastic, and PETE plastic bottles showed significant effect on moisture content, pH, TPC, and organoleptic in room temperature storage at 27-32 °C but it had no significant effect in the refrigerator temperature storage at 12-15 °C. The difference in storage temperature affects the occurrence of deviation or alteration of lemea quality.